Persepsi Wisatawan terhadap Daya Tarik dan Citra Kuliner Lokal: Studi Kasus Kedai Susu Pak No sebagai Destinasi Wisata di Pacet - Achmad Bintang Burhanuddin; Mohammad Insan Romadhan (Yayasan Cendekia Gagayunan Indonesia, 2025)
Kedai Susu Pak No is a well-known local culinary destination in the tourist area of Pacet, Mojokerto. The place offers a distinctive culinary experience with a cool mountain atmosphere and authentic fresh milk. This study aims to evaluate tourists' perceptions of the culinary appeal and image of Kedai Susu Pak No, as well as assess the effectiveness of its promotional strategies. A descriptive qualitative approach with a case study method was used. Data were collected through in-depth interviews with five purposively selected tourists. Findings indicate that tourists generally have a positive perception of the venue, especially regarding the ambiance, taste quality, and affordability. However, limited facilities such as parking and underutilized digital promotion channels are noted as weaknesses. Thus, improving social media-based promotion and strengthening visual identity are necessary to enhance the image of Kedai Susu Pak No as a leading local culinary destination in Pacet.